A Numerical Study on Unsteady Natural Convection Flow with Temperature Dependent Thermal Conductivity past an Isothermal Vertical Cylinder - S.F.Ahmmed, Md. A Hossain, R.K.Mondal , (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper represents a numerical investigation of the effect of temperature dependent thermal conductivity on unsteadynaturalconvection flow past a semi-infinite isothermal vertical cylinder immersed in air. The thermal conductivity is adopted tovary thetemperature. The governing non-dimensional boundary layer equations have been solved numerically employing anexplicit finitedifference method. To interpret the influence of variable thermal conductivity on the velocity and temperatureprofiles aparametric study is accomplished. The numerical consequences disclose that the thermal conductivity has significantinfluence ontransient velocity and temperature profiles, average skin friction coefficient and average heat transfer rate. Theconclusionindicates that when the thermal conductivity parameter increases the temperature and skin friction coefficient increasesbut thevelocity near the wall and Nusselt number decreases. We have also shown the effect of thermal conductivity variationparameteron isotherms and streamlines